Die ADHS der Sonderpädagogik Zur diskursiven Konstruktion des ,Nicht_Normalen' auf der Ebene disziplinärer Wissensbestände - Haas, Benjamin (Perspektiven sonderpädagogischer Forschung, 2021)
The present study focuses on the question of how the discipline of special education producesknowledge on the subject of ADHD and thereby creates a specific reality of the phenomenon. Due to the observation that in schools the label ADHD is used as 'catch-all-typology' and a generalisation for abnormal behaviours, it is questioned how ADHD is constructed as a categoryof 'not_normal' behaviour within special educational literature. Therefore, an understanding of disability that is inspired by a cultural studies perspective will be applied to the production of knowledge in the field of special education. The goal is to identify institutionalised processes of exclusion and to highlight the necessity of a modified conceptualization of the 'not_normal'. Transferring perspectives of dis_ability studies to the field of special education, the analysis can be placed within the context of dis_ability studies in education. This supports a differencetheoretical inspired and theoretically founded, empirical research on the subject of inclusion. The body of investigation includes 74 articles published in special education journals and handbooks between 2000 and 2015. The articles have been examined by a critical perspective on power relations and the construction of normality with a discourse analytical concept. As a result, not only the discursive construction of the subject ADHD can be reconstructed. Moreover, it can be shown, how in the discourse of special education 'normal' behaviour is differentiated from 'not_normal' behaviour, how the students being marked as 'not_normal' are requested to re-integrate into the normal zone and which invocations follow this discussion. The findings demonstrate, that the construction of the 'not_normal' in the discourse of special education secures prevailing norms in school and that this is accompanied by individualistic attributions and constraints.